The Role of Genetics and Oxidative Stress in the Etiology of Male Infertility—A Unifying Hypothesis? - Aitken, Robert John; Baker, Mark A. (Frontiers in Endocrinology, 2020)
Despite the high prevalence of male infertility, very little is known about its etiology. In recent years however, advances in gene sequencing technology have enabled us to identify a large number of rare single point mutations responsible for impeding all aspects of male reproduction from its embryonic origins, through the endocrine regulation of spermatogenesis to germ cell differentiation and sperm function. Such monogenic mutations aside, the most common genetic causes of male infertility are aneuploidies such as Klinefelter syndrome and Y-chromosome mutations which together account for around 20–25% of all cases of non-obstructive azoospermia. Oxidative stress has also emerged as a major cause of male fertility with at least 40% of patients exhibiting some evidence of redox attack, resulting in high levels of lipid peroxidation and oxidative DNA damage in the form of 8-hydroxy-2'-deoxyguanosine (8OHdG). The latter is highly mutagenic and may contribute to de novo mutations in our species, 75% of which are known to occur in the male germ line. An examination of 8OHdG lesions in the human sperm genome has revealed ~9,000 genomic regions vulnerable to oxidative attack in spermatozoa. While these oxidized bases are generally spread widely across the genome, a particular region on chromosome 15 appears to be a hot spot for oxidative attack. This locus maps to a genetic location which has linkages to male infertility, cancer, imprinting disorders and a variety of behavioral conditions (autism, bipolar disease, spontaneous schizophrenia) which have been linked to the age of the father at the moment of conception. We present a hypothesis whereby a number of environmental, lifestyle and clinical factors conspire to induce oxidative DNA damage in the male germ line which then triggers the formation de novo mutations which can have a major impact on the health of the offspring including their subsequent fertility.